2015
DOI: 10.1021/acscatal.5b00644
|View full text |Cite
|
Sign up to set email alerts
|

Photocatalytic Oxidation of Benzyl Alcohol by Homogeneous CuCl2/Solvent: A Model System to Explore the Role of Molecular Oxygen

Abstract: Photocatalytic Reactions of Typical Alcohols under Different Conditions and the Hydrogen Kinetic Isotope Effects (KIEs)……………………………………………………………….…S2-S8 UV-Vis Absorption Spectroscopies of Copper/Solvents Systems…………………………...……S9 Isotopic Experimental Section…………………………………………………...……………… S10 Mechanism of the Dehydrogenation Reactions by Copper Complex and Pt/TiO 2 ……….S11-S12 Mass Spectra Corresponding to the Products of Different Reactions………………….…S13-S33

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
46
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(47 citation statements)
references
References 37 publications
0
46
0
1
Order By: Relevance
“…Although doubly labeled products were also observed, the unlabeled form was most likely generated by H/D exchange between the 18 O-labeled products and water. [12] The oxidative cleavage of indoles is a light-dependent process, as demonstrated by the experimental results shown in Figure 1. The yield of the model reaction under visible light increased over time, whereas there was no enhancement in the yield when the reaction mixture was stirred in the dark.…”
Section: Resultsmentioning
confidence: 91%
See 1 more Smart Citation
“…Although doubly labeled products were also observed, the unlabeled form was most likely generated by H/D exchange between the 18 O-labeled products and water. [12] The oxidative cleavage of indoles is a light-dependent process, as demonstrated by the experimental results shown in Figure 1. The yield of the model reaction under visible light increased over time, whereas there was no enhancement in the yield when the reaction mixture was stirred in the dark.…”
Section: Resultsmentioning
confidence: 91%
“…In all of the cases, HRMS analysis revealed the major product to contain one 18 O atom. Although doubly labeled products were also observed, the unlabeled form was most likely generated by H/D exchange between the 18 O‐labeled products and water …”
Section: Resultsmentioning
confidence: 99%
“…Low yields and poor selectivity have been the main drawbacks associated with catalytic oxidation reactions. Recently, the selective oxidation of benzyl alcohols to benzaldehyde by using iron oxide-based nanocomposites [17], ionic liquid-modified MIL-100(Fe) [18], developed copper(Ι)/TEMPO catalysts (TEMPO = 2,2,6,6-tetramethylpiperidinyl-N-oxyl) [19,20], photocatalytic oxidation by homogeneous CuCl2 [21], metal-free systems [22], photoactive VO@g-C3N4 [23] and Co oxide nanoparticles [24], among others have been reported.…”
Section: Introductionmentioning
confidence: 99%
“…15 Among green transformations, light-assisted oxidations using air or molecular oxygen (O2) as the oxidant represents an interesting example, as it has been shown that the SPR excited hot electrons can efficiently activate molecular oxygen. [16][17][18][19] In addition to the metal nanoparticles or active phase, it is well-established that optimizing metal-support interactions is an efficient strategy to the improvement of performances in nanocatalysis. 20,21 Among the several supports, CeO2 has been widely employed in oxidation reactions due to its oxygen mobility and storage properties, which can be further enhanced at the metal-support interface due to metal-support interactions.…”
Section: Introductionmentioning
confidence: 99%